On the microstructure evolution of AA6061 with pulsed laser powder bed fusion - Sivaji Karna; Lang Yuan; Tianyu Zhang; Andrew J. Gross; Daniel Morrall; Timothy Krentz; Dale Hitchcock (Materials Research Letters)
This study uncovers new opportunities for microstructure engineering of AA6061 using pulsed lasers in powder bed fusion. Experimental analysis reveals that pulsed lasers allow for extensive control of grain sizes. Lower frequencies or duty cycles induce remelting cycles that promote finer grains and homogenized subgrain structures, while higher frequencies with high duty cycles sustain elevated temperatures, reducing cooling rates and resulting in coarser grains. Pulsing strategy is demonstrated as facile route for tailoring microstructure through enhanced control over solidification. These findings present an effective means in additive manufacturing by linking pulsed laser dynamics to microstructure evolution towards desired material properties.